Ontheemd - Petterson, Jennifer (Netherlands : CPS Films, IKON, 2009)
What moves Western aid-workers to go to the most remote, inhospitable and dangerous places in the world to help other people? What are their true motives and can they really make a difference? In Yei, a small town in Southern Sudan, a large part of the population is returning to their homes now that the civil war has ended. It is one of the poorest parts of the world, virtually without infrastructure. Six Western aid-workers are trying to help the refugees build a new life. With unprecedented candor they talk about their ideals, doubts, disappointments and desires.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films